Excel X : for Mac OS X - Langer, Maria (Visual quickstart guide., 2002)
Excel X for Mac OS X is the model OS X app, from its Aqua interface to its complete support for OS X's modern architecture. In Excel X for Mac OS X: Visual QuickStart Guide, author Maria Langer, veteran Mac writer and consultant, walks you through all that's new and noteworthy in Microsoft's spreadsheet powerhouse, dispensing lots of expert tips along the way. Maria knows you're a busy professional. That's why Excel X for Mac OS X: VQS was designed to let you learn as you work. Use it as a quick-reference guide: Just look up a topic in the index--or use the page tabs to thumb to it--then follow the simple, concise steps and check your results against the accompanying screenshots. Newcomers can treat the book as a step-by-step introduction to Excel, starting with the basics, then moving on to more advanced techniques, such as inserting objects and multimedia events, creating charts and graphs, and publishing spreadsheets to the Web.